Acute scrotal swelling following perforated rectal carcinoma with abscess formation - Chauhan, Vishnusai (BJR Case Rep, 2016)
A 59-year-old cachectic male was referred to the surgical outpatient department with intermittent haematochezia and a longstanding change in bowel habit with associated weight loss and anaemia. Following investigation, he was diagnosed with a large rectal tumour with multiple metastases. 7 days later, the patient presented again with fevers, bilious vomiting, abdominal pain and distension. On examination, he had a generally tender abdomen,= although no peritonism, but an enlarged, extremely tender hemiscrotum with no cough reflex. Imaging revealed a perforated rectum and subsequent abscess formation, which tracked via an unusual anatomical route to present as scrotal swelling.